1979
DOI: 10.1159/000117676
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interhemispheric Differences in Relation to Various Psychopathological Components of the Depressive Syndromes

Abstract: Previous investigations from our laboratory have suggested a possible interhemispheric difference in brain functioning in relation to the severity of a depressive psychopathological process. The present study has been carried out to extend the previous fìndings to comprise a more detailed symptom analysis of the depressive syndrome, several EEG characteristics, and a new method of EEG analysis. 22 depressed patients, most of them previously untreated, participated in the study. The patients were rated by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
2
4
1
Order By: Relevance
“…Although a number of studies have demonstrated an activity asymmetry between left and right hemispheres in patients with major depression by the means of neuroimaging (Bench et al, 1995;Mottaghy et al, 2002), TMS (Bajbouj et al, 2006;Fitzgerald et al, 2004;Maeda et al, 2000), cognitive tasks (Bermpohl et al, 2006) and electroencephalogram (Monakhov et al, 1979); our baseline data failed to show such an asymmetry (i.e., there was no difference in the baseline MT between the left and right hemisphere at baseline). One possibility for this difference might be different characteristics of depression; such as depression severity.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Although a number of studies have demonstrated an activity asymmetry between left and right hemispheres in patients with major depression by the means of neuroimaging (Bench et al, 1995;Mottaghy et al, 2002), TMS (Bajbouj et al, 2006;Fitzgerald et al, 2004;Maeda et al, 2000), cognitive tasks (Bermpohl et al, 2006) and electroencephalogram (Monakhov et al, 1979); our baseline data failed to show such an asymmetry (i.e., there was no difference in the baseline MT between the left and right hemisphere at baseline). One possibility for this difference might be different characteristics of depression; such as depression severity.…”
Section: Discussioncontrasting
confidence: 83%
“…These findings were later confirmed by Fitzgerald et al (2004) and Bajbouj et al (2006). Finally similar lateralized differences in brain activity in depressed patients have been reported by electroencephalographic studies (Matousek, 1991;Monakhov et al, 1979).…”
supporting
confidence: 78%
“…From this standpoint, multivariate analysis techniques have been applied to electroencephalographic or biochemical data since the 1970’ in order to develop high-sensitivity and accuracy models for the diagnosis of mental disorders (Bochkarev et al, 1987; Lazarev, 2006; Lazarev et al, 1990; Monakhov et al, 1979; Schwarz et al, 2010). However, in order to explain these complex mental conditions in terms of biological correlates, a substantially larger sample of subjects than those set of variables is required.…”
Section: Introductionmentioning
confidence: 99%
“…This approach demonstrated substantial resolving power in differentiating endogenous mental diseases and pathological functional states during therapy (Nikiforov and Bochkarev, 1974;Monakhov et al, 1979;Bochkarev et al, 1987). It should be noted, however, that the method was considered as advantageous in comparison with the integral spectral characteristics of a broad standard band as a whole and only with respect to the index and amplitude separation.…”
Section: The Factor Structure Of Eeg Frequency and Amplitude Parametersmentioning
confidence: 99%